Effect of Absorption and Scattering on Fluorescence of Buried Tumours - Kawthar M. K. Alghourani; Wesam Bachir; George Karraz (Journal of Spectroscopy)
Fluorescence spectroscopy is widely used for biomedical optical diagnosis and surgical resection of tumours. This work investigates laser-induced fluorescence spectroscopy of fluorescence inclusions that are embedded in turbid media. 405 nm laser diode is used for exciting buried protoporphyrin- (PpIX) based inclusions in brain-like optical phantoms. Effects of scattering and absorption of the turbid medium on the recorded fluorescence signal and depth-resolved fluorescence were studied. Results show that optical properties of the surrounding turbid medium influence the intensity of the fluorescence signal. Absorption coefficient of the surrounding medium is the major contributor to the fluorescent signal. Analysis of the recorded fluorescence spectra shows that the effect of absorption coefficient is larger than the effect of scattering coefficient on the fluorescence intensity by nearly fivefold. The findings indicate that the fluorescence signal could be used as a biomarker of optical property variations through different stages of malignancy. This can enhance the detectability of malignant tissue for diagnostic and surgical purposes as well.